RAPD-markers assisted genetic diversity analysis and Bt-Cry1Ac gene identification in eggplant (Solanum melongena L.) - Rokibul Hasan; Md Atikur Rahman; Ahmad Humayan Kabir; F M Ali Haydar; Md Abu Reza (Plant Trends)
Generic diversity (GD) screening helps to identify candidate genes involved in diseases, pests, or other stress resistance in plants. GD is crucial for maintaining vigor and healthy plant population. The random amplified polymorphic DNA (RAPD) is a rapid polymerase chain reaction (PCR)-based molecular marker, effective for screening genetic diversity in diverse plant species. In this study, we applied the RAPD-markers-assisted PCR approach to explore genetic diversity (GD) among 7 varieties of eggplant (Solanum melongena L.) at DNA level. Further, we assessed the presence of Bt-Cry1Ac gene in those varieties using the PCR approach. The eggplants showed genetic diversity at the DNA level. The amplification with two RAPD primers (OPA-02, OPA-04) produced a total of 41 bands. The highest similarity showed 78.57% among sample 4 (Eggplant China) vs sample 7 (Purple king F1) and sample 1 (Eggplant Srilanka) vs sample 4 (Eggplant China), while the lowest was 28.57% among sample 7 (Purple king F1) vs sample 3 (Eggplant Chittagong-1). In addition, the PCR results for the Bt Cry1Ac primer did not show a considerable band in the expected amplicon size. The dendrogram showed the genetic variability and relationship among all seven eggplant varieties at the genetic level. The study formulated a simple marker-based method for an effective molecular protocol to study genetics in eggplants. It also reported the presence of the Bt gene in popular eggplant varieties. [Plant Trends 2023; 1(1.000): 20-30]